Continental concerted efforts to control the seventh outbreak of Ebola Virus disease in Uganda: The first 90 days of the response - Jane R. Aceng; Henry K. Bosa; Neema Kamara; Diana Atwine; Henry Mwebesa; Howard Nyika; Katusiime Maureen; Charles Olaro; Atek Kagirita; Mohammed Larmode; Lul p. Riek; Elvis Temfack; et al. (AOSIS, 2023)
On 20th September 2022, Uganda declared the 7th outbreak of Ebola virus disease (EVD) caused by the Sudan Ebola strain following the confirmation of a case admitted at Mubende Regional Referral Hospital. Upon confirmation, the Government of Uganda immediately activated the national incident management system to initiate response activities. Additionally, a multi‑country emergency stakeholder meeting was held in Kampala; convening Ministers of Health from neighbouring Member States to undertake cross‑border preparedness and response actions. The outbreak spanned 69 days and recorded 164 cases (142 confirmed, 22 probable), 87 recoveries and 77 deaths (case fatality ratio of 47%). Nine out of 136 districts were affected with transmission taking place in 5 districts but spilling over in 4 districts without secondary transmission. As part of the response, the Government galvanised robust community mobilisation and initiated assessment of medical counter measures including therapeutics, new diagnostics and vaccines. This paper highlights the response actions that contributed to the containment of this outbreak in addition to the challenges faced with a special focus on key recommendations for better control of future outbreaks.